Ответы и объяснения

2013-01-28T11:40:06+00:00

a) 9x-6(x-1)=5(x+2)

     9x-6x+6=5x+10

     3x-5x=10-6

     -2x=4

     x=-2

 

 

б)    (3x - 1)/6 -  x/3 =( 5-x)/9

        (3x - 1)/6 -  x/3 -( 5-x)/9 =0

       3 (3x - 1)-  6x -2( 5-x)=0 

        9x-3-6x-10+2x=0

       5x-13=0

       5x=13

       x=13/5

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

2013-01-28T11:43:33+00:00

 

a) 9x-6(x-1)=5(x+2)

9x-6x+1=5x+10

2x=-9

x=-4,5

 

б)

3(3x-1)-6x=2(5-x)

9x-3-6x=10-2x

5x=13

x=2,6